Analisis Profil Naratif Berbasis Gender: Aspek Produksi, Kompleksitas Sintaksis dan Penggunaan Bahasa pada Dewasa - Hanandita, Virginia (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Narrative analysis serves as a fundamental component in assessing language proficiency. From a Speech-Language Pathology (SLP) perspective, gender is considered a potential influencing factor on an individual's narrative profile, particularly affecting speech output and syntactic complexity. This study compared the narrative skills of adult male and female participants.Objectives: This research aims to analyze and compare the narrative skills of adult male and female participants by examining output quantity, syntactic complexity, and vocabulary usage in stories generated from the wordless picture book Frog, Where Are You?. Methods: This study utilized a descriptive qualitative approach with a comparative case study design. It involved two adult participants, one male and one female, both aged 34. Narrative data was collected using the wordless picture book